Stimulation of Human Innate Immune Defenses by Bacteria in vitro - Badi Salih AL-tmemi, Manal (University of Thi-Qar Journal of Science, 2010)
The microflora is essential for immune education and amplification of lymphoid effectorcells, mainly at the mucosal level. It is well documented that the efficacy of the mucosalimmune system can be significantly impaired in germ-free animals. In this study the bacteriaused as antigens (mitogen) to the stimulation of human immune cells in vitro. Gram-positiveStreptococci spp and gram-negative Escherichia coli was investigated. The stimulation ofhuman peripheral blood mononuclear cells by the various bacterial strains induced a differentialcytokine pattern. Streptococci and E. coli significantly (P ≤ 0.001) induced gamma interferon(IFN- ) and interleukin-12 (IL-12). All bacteria mediated the proliferation of human peripheralblood mononuclear cells. Proliferate activity of lymphocytes was observed when mitogens wereadded. The MTT is employed to assess the response of lymphocytes to a mitogen. Bacteria andPHA was effective in inducing the MTT index of lymphocytes. Therefore, PHA, gram-positivebacteria, and gram-negative bacteria showed a high significant (P ≤ 0.001) increased percentageof MTT index (96.4, 88.2 and 74.7 %, respectively) as compared to control subjects (42.5%)with no treatment.